Designing a scratch media to increase tenth-graders’ collaborative and communicative English learning and teacher’s teaching - Rohmi Juharoh; Didik Rinan Sumekto; Silvester Goridus Sukur; Dita Surwanti; Khayri Amir Alkashtawi (Journal of English Language and Pedagogy, 2022)
As a learning media, scratch conditionally becomes a suitable learning animation for student of six to sixteen years old. This study aims to examine the role of media to enhance the tenth-graders’ understanding of the material that is being delivered by the English teacher, while presenting communication and collaboration between teacher - students and students - students are engaged in. Data collection used interview and scratch practices with an analysis, design, development, implementation, and evaluation (ADDIE) model to employ this study. The findings showed that scratch media was fun, enthusiastic, interactive, and effective for learning English. Scratch model enrolled modification in making quizzes with the learning materials, in which the learning activities connected with the content, characters, background, and grammar. Scratch modification had shown the suitability of images, expressions, gestures, and characters that could change and move, as well as the suitability of the material and background. Besides that, the teacher added various sounds or back sounds the tenth-graders made students more enthusiastic and interesting with the quizzes. The use of scratch modified the animation, the background, the back sound, and all the features, in which it has a positive influence on tenth-graders’ learning effectiveness, materials absorption, and interest.